(untitled) (Research, Society and Development, 2024)
Technological resources inaugurated a standard economic order, called surveillance capitalism from the perspective of Shoshana Zuboof. Characterized by informational curation, the new model is the result of prediction that is made possible with the capture and use of personal data for commercial purposes. The new social enclosure caused by the formation of informational bubbles is, today, one of the phenomena of amplification of political polarization and, consequently, of the dissemination of hate speech. The radicalization of debates, the mismatch of different ideas and the manipulation of personal data for unknown purposes by internet users are necessary confrontation points for understanding the harmful interference of technology on modern democracy. So, the objective of this study is to understand whether informational curation is related to the increasing polarization and the spread of extremist discourses observed in recent years.